EVALUATING OPTIMAL CAPITAL STRUCTURE OF PT MATAHARI PUTRA PRIMA TBK (MPPA) - Saputra, Hendrie
This thesis investigates evaluating the optimal capital structure of PT Matahari Putra Prima Tbk (MPPA). By employing a comprehensive analysis that integrates both external and internal factors affecting the company, this study aims to evaluate the financial stability and overall capital strategy of MPPA. The research utilizes a combination of PESTLE analysis, Porter’s Five Forces, financial ratio analysis, and Altman Z-score to assess the company's current standing and future projections. Various scenarios are projected, including best, base, and worst-case outcomes, to determine the optimal capital structure under different conditions. Additionally, sensitivity analysis is conducted to understand the robustness of the capital structure against market volatility. The findings suggest strategic recommendations for MPPA to enhance its capital efficiency and investor attractiveness, highlighting the importance of rights issues in maintaining financial health and supporting long-term growth. This study contributes to the broader understanding of capital structure optimization in the context of Indonesian retail companies and provides actionable insights for corporate finance practitioners and policymakers.